Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300790
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically Compensating Effect of End-to-End Latency in Moving-Target Selection Games

Abstract: Effects of unintended latency on gamer performance have been reported. End-to-end latency can be corrected by postinput manipulation of activation times, but this gives the player unnatural gameplay experience. For moving-target selection games such as Flappy Bird, the paper presents a predictive model of latency on error rate and a novel compensation method for the latency effects by adjusting the game's geometry design-e.g., by modifying the size of the selection region. Without manipulation of the game cloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 47 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…Related works have shown that the MT increases as a target's speed V increases [24,26,34]. For error rate prediction, naturally, as the V increases, users are more likely to fail a task [30,32,33,39,50].…”
Section: Related Work Success or Error Rate Prediction Models For Poimentioning
confidence: 99%
“…Related works have shown that the MT increases as a target's speed V increases [24,26,34]. For error rate prediction, naturally, as the V increases, users are more likely to fail a task [30,32,33,39,50].…”
Section: Related Work Success or Error Rate Prediction Models For Poimentioning
confidence: 99%
“…While Wobbrock et al applied a time limit as an objective constraint by using a metronome in their study [54], this speed-accuracy tradeoff was also valid when the priority was subjectively biased [63]. Besides the case of rapidly aimed movements, the error rate has also been investigated for tapping on a static Model 205:3 button within a given temporal window [30][31][32]. Despite the recent importance of finger-touch operations on smartphones and tablets, however, the only model for predicting the success rate while accounting for finger-touch ambiguity is the work by Bi and Zhai on pointing from an off-screen start [10].…”
Section: Success-rate Prediction For Pointing Tasksmentioning
confidence: 99%
“…Lee et al [82] propose adjusting the geometry of a game world based on latency. Speciically, they adjust the gap distance between pipes based on latency for the game Flappy Bird.…”
Section: Atributementioning
confidence: 99%